De l’analyse des émotions comme risque à la construction de la santé par la coloration collective des affects et des situations - Marc Loriol (Perspectives Interdisciplinaires sur le Travail et la Santé)
The management of emotions, especially in service jobs, is often analyzed as a risk. The notion of emotional labour, developed by Arlie Russell Hochschild, also encourages us to see working on one's emotions and those of others as a task that should be remunerated. That said, the emotional dimension of work relationships can also be rewarding. The collective regulation of emotions at work can act on the valence of affects, give meaning to the efforts made, increase the workers' ability to act and gain control over the situation, and, thereby, participate in the construction of their health. After briefly reviewing the various studies on the collective regulation of emotions and health, this article focuses on a particular aspect of this regulation: the affective colouring of situations which aims to influence the valence, meaning, and traumatic and euphoric imprint of the affects. Potentially disruptive emotions such as fear, humiliation, and anger can then be used as a lever to valorize action, support prudent know-how, and repair damaged identities. Research with police officers, diplomats, and industrial workers illustrates and supports this hypothesis.